2019
DOI: 10.1186/s12903-019-0994-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two forms of chlorhexidine on the accuracy of contemporary electronic apex locators

Abstract: BackgroundAccurate determination of working length (WL) is crucial for the success of endodontic therapy. The aim of this study was to determine the influence of 2% chlorhexidine digluconate solution, 2% chlorhexidine digluconate gel and 2% hypochlorite solution on the accuracy of two devices: the Raypex 5 and the ApexDal.MethodsTwenty-nine single-rooted human teeth were used in this study. The crowns were cut horizontally and embedded in an alginate mass. In each tooth, six endodontic measurements were made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 55 publications
1
7
0
11
Order By: Relevance
“…In present study, the results showed that both EALs had no significant difference in detection of both perforations which is consistent with previous studies tested the same idea. Root ZX mini demonstrates consistent and accurate reading of root canal length and determination of apical constriction in presence of NaOCl and CHX (4,5,6,7,9,10,11,14,15,23,24) in addition the presence of 2% Chlorhexidine in the root canal did not affect the accuracy of both EALs used in this study.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In present study, the results showed that both EALs had no significant difference in detection of both perforations which is consistent with previous studies tested the same idea. Root ZX mini demonstrates consistent and accurate reading of root canal length and determination of apical constriction in presence of NaOCl and CHX (4,5,6,7,9,10,11,14,15,23,24) in addition the presence of 2% Chlorhexidine in the root canal did not affect the accuracy of both EALs used in this study.…”
Section: Resultsmentioning
confidence: 62%
“…Various electroconductive materials have been used such as agar-agar, alginate, gelatin, and a saline solution for in vitro evaluation of EALs in perforated teeth (6)(7)14) . In this study, alginate was selected as the embedding medium to simulate the periodontium because it is easy to handle, rigid, has firm consistency that prevent intrusion of the material into perforation, remains around the root, simulates the periodontal ligament with its colloidal consistency, and presents suitable electroconductivity (23). The rigid alginate firmly supported the teeth and permitted experiment to be performed with the roots embedded.…”
Section: Resultsmentioning
confidence: 99%
“…Nesse sentido, a determinação bem sucedida do comprimento de trabalho contribui com maior índice de sucesso do tratamento endodôntico (MAREK et al, 2020;SCARPARO, 2020;BOLAM et al, 2018). O método radiográfico é o mais utilizado na literatura para a obtenção de informações para determinar a odontometria (NÓBREGA et al, 2016;MAREK et al, 2020;SCARPARO, 2020;SILVA, 2018;VENANTE et al, 2017;EL SAMAN, 2016), porém, existe uma concordância entre pesquisadores que a técnica é limitada, apresentando desvantagens, como imagem bidimensional com estrutura tridimensional, imagem distorcida, sobreposição de estruturas anatômicas, exposição do paciente à radiação e induz a falhas de interpretação do operador (NÓBREGA et al, 2016;MAREK et al, 2020;SCARPARO, 2020;BOLAM et al, 2018;SILVA, 2018;EL SAMAN, 2016;VENANTE et al, 2017).…”
Section: Resultsunclassified
“…Quanto ao método eletrônico com o uso de localizadores apicais, a maioria dos dispositivos de medição eletrônicos são baseados na teoria de Suzuki et al (1942), que determinaram que a resistência elétrica entre a mucosa oral e os tecidos periodontais foi constante em 6,5 kΩ, independentemente da idade do paciente ou morfologia dentária (MAREK et al, 2020;SCARPARO, 2020;SILVA, 2018;EL SAMAN, 2016;VENANTE et al 2017). Foi a partir desta teoria que Sunada (1962), construiu o primeiro LAE, que demonstrou imprecisões nas leituras de eletrólitos ou tecidos pulpares vitais (MAREK et al, 2020), porém, ainda assim, a introdução destes mecanismos tem sido confiado com o papel fundamental na determinação do comprimento do canal radicular, mesmo diferindo dos originalmente propostos (OLIVEIRA et al, 2017).…”
Section: Resultsunclassified
See 1 more Smart Citation